Suffering of the Serbian Orthodox Church in the Independent State of Croatia - Janjić, Jovan (Napredak, 2022)
The church is a spiritual institution in which a believing man fulfills his spiritual needs and, accordingly to that, he builds his spiritual being. The church consists of the clergy and the believing people. Without a faithful people there is no Church. And therefore, everything that concerns the Church concerns the faithful people; and vice versa, all that concerns the faithful people, it concerns the Church. In the territory of the clero-fascist Independent State of Croatia (NDH), persecution, terror and killing were burned and the people and the Church. Serbs were killed not only because they were other nations, because of their national being, but also because they have different faiths, because of their spiritual being. They were killed both because they are Serbs and because they are Orthodox. The Ustasha program itself points to this, publicly declared through the words of the leader of the Ustasha state. Genocide Ustasha program in relation to the Serbs - to kill one third, to expel one third, and to one third converted to Catholicism - a clear reference to the planned activities to make Serbs both spiritually and physically kill. If a person’s faith is attacked, if it is reckoned with the fact that a person will be induced or forced to renounces his faith in order to accept someone else’s, then that is spiritual killing - killing a man as he is was until then. This was precisely the goal of the forced Catholicization of Orthodox Serbs in the NDH. It was done according to the declared Ustasha program. And for the sake of its greatest possible achievement, the Serbian Orthodox Church was particularly under attacк.